College algebra - Rees, Paul K. (New York : McGraw-Hill Publishing Company, 1990)
In this text, we cover all the standard topics for a college algebra text in a straightforward manner. The tenth edition is a substantial revision, which maintain the character of our earlier editions. Many new examples added.
Chapter1. The real number system -- Chapter2. Polynomials -- Chapter3. Fractions -- Chapter4. Rational exponents and radicals -- Chapter5. Linear and quadratic equations and inequalities -- Chapter6. Graphs and functions -- Chapter8. Exponential and logarithmic function -- Chapter9. Systems of equations and inequalities -- Chapter10. Matrices and determinant -- Chapter11. Sequences and series -- Chapter12. Topics in algebra -- Chapter13. The conics .
Includes index.
Keywords: COLLEGE ALGEBRA